Towards a More Complete and Accurate Experimental Nuclear Reaction Data Library (EXFOR): International Collaboration Between Nuclear Reaction Data Centres (NRDC) - Otuka, N.; Dupont, E.; Semkova, V.; Pritychenko, B.; Blokhin, A.I.; Aikawa, M.; Babykina, S.; Bossant, M.; Chen, G.; Dunaeva, S.; Forrest, R.A.; Fukahori, T.; et al. (Nuclear data sheets, 2014)
The International Network of Nuclear Reaction Data Centres (NRDC) coordinated by the IAEA Nuclear Data Section (NDS) successfully collaborates in the maintenance and development of the EXFOR library. As the scope of published data expands (e.g. to higher energy, to heavier projectile) to meet the needs of research and applications, it has become a challenging task to maintain both the completeness and accuracy of the EXFOR library. Evolution of the library highlighting recent developments is described.